Diagnostic Criteria and Treatment Modalities of Ectopic Pregnancies: A Literature Review - Ibrahim A. Abdelazim; Mohannad AbuFaza; Svetlana Shikanova; Bakyt Karimova (European Medical Journal, 2021)
Background: Ruptured ectopic or extrauterine pregnancy (EP) is responsible for 6% of maternal deaths in the first trimester. This review was designed to summarise the diagnostic criteria and treatment modalities of EPs. Methods: Recent guidelines of the international societies of obstetrics and gynaecology, including the Royal College of Obstetricians and Gynaecologists (RCOG), the American College of Obstetricians and Gynecologists (ACOG), and the European Society of Human Reproduction and Embryology (ESHRE), were reviewed to summarise the diagnostic criteria and treatment modalities of EPs. Results: A minimum β-human chorionic gonadotropin (β-hCG) rise of ≥35% in 48 hours was suggested to diagnose intrauterine pregnancy. A β-hCG rise <35% in 48 hours has 96.2% positive predictive value, 69.7% negative predictive value, and 80.2% overall accuracy in predicting EPs. The blob sign has >90% positive predictive value in diagnosing EPs in symptomatic females with positive β-hCG and no definite intrauterine gestational sac by transvaginal sonography. The interstitial ectopic pregnancy and cornual pregnancy are two separate entities of EPs. Interstitial line sign has 80% sensitivity and 98% specificity in diagnosing interstitial ectopic pregnancy. A meta-analysis reported 89% overall success rate for methotrexate in treatment of EPs; the multi-dose regimen was significantly more successful than the single-dose regimen. Conclusion: Institutes and healthcare providers should follow clear guidelines and/or protocols for the management of EPs. Institutes should implement competency-directed training programmes to increase healthcare providers' skills to diagnose and treat EP variants using different modalities.